Major risk factors and histopathological profile of treatment failure, relapse and chronic patients with anthroponotic cutaneous leishmaniasis: A prospective case-control study on treatment outcome and their medical importance. - Mehdi Bamorovat; Iraj Sharifi; Shahriar Dabiri; Simin Shamsi Meymandi; Ali Karamoozian; Rezvan Amiri; Amireh Heshmatkhah; Mehdi Borhani Zarandi; Mohammad Reza Aflatoonian; Fatemeh Sharifi; Reza Kheirandish; Saeid Hassanzadeh (Public Library of Science (PLoS), 2021)
Over the last years, there has been a remarkable increase in the number of unresponsive patients with anthroponotic cutaneous leishmaniasis (ACL) reported worldwide. The primary objective of this study was to explore the role of demographic, clinical and environmental risk related-factors in the development of treatment failure, relapse and chronic cases compared to responsive patients with ACL. Moreover, molecular, histopathological and immunohistochemical (IHC) findings between these forms were explored. This work was undertaken as a prospective and case-control study in southeastern Iran. Culture media and nested PCR were used to identify the causative agent. Univariate multinomial and multiple multinomial logistic regression models and the backward elimination stepwise method were applied to analyze the data. A P<0.05 was defined as significant. Also, for different groups, skin punch biopsies were used to study the histopathological and immunohistochemical (IHC) profile. All samples showed that L. tropica was the only etiological agent in all unresponsive and responsive patients with ACL. Data analysis represented that 8 major risk factors including nationality, age groups, occupation, marital status, history of chronic diseases, duration of the lesion, the lesion on face and presence of domestic animals in the house were significantly associated with the induction of unresponsive forms. The histopathological and immunohistochemical findings were different from one form to another. The present findings clearly demonstrated a positive relation between ACL and distinct demographic, clinical and environmental risk determinants. Knowledge of the main risk factors for ACL infection is crucial in improving clinical and public health strategies and monitor such perplexing factors.